Cocaine and Sleep: Early Abstinence. (2007) - Morgan, Peter T.; Malison, Robert T.
Abstract : Compulsive cocaine use is associated with a profound dysregulation of sleep. Perhaps the result of chronic use, a significant deterioration in sleep is apparent over the first 3 weeks of abstinence, with no indication of recovery. Interestingly, the diminished sleep is not accompanied by subjective reports of poor or worsening sleep. Rather, subjective reports actually improve over abstinence, while sleep-related cognitive performance declines. A mechanistic understanding of the apparent difference in objective and subjective measures is currently lacking. Here we review the relevant literature on cocaine use and sleep, and discuss the possible relevance of this sleep disturbance in relationship to the underlying disorder and its treatment.